(untitled) (Research, Society and Development, 2021)
Objectives: To analyze existing scientific evidence that describes the genotoxic, mutagenic or cytotoxic effects associated with those collected in the Doce river basin, after the dam burst. And to analyze a cancer mortality rate (CM) among a population of Mariana, Governador Valadares (GV) and Ipatinga, in Minas Gerais, and Colatina and Linhares, in Espirito Santo, cities related to the Doce river. Methods: Five databases were used: PubMed, SciELO, Science Direct, Scopus and Google Scholar, the descriptors: “Dam”, “Fundao”, “Mariana”, “genotoxic” and boolean operator “AND”, study studies that described the toxic effects of collected in the Doce river. In addition, CM data were collected from INCA’s “On-Line Mortality Atlas”, for the periods 2013-2015 and 2016-2018, reported in the cities studied. Results: Four studies were selected on the genotoxic effects. The rates of CM employees per 100,000 inhabitants in the cities mentioned and defined above, there were increases in GV, Ipatinga, Colatina and Linhares, but reduction in Mariana. Conclusion: It is suggested that the analyzed ones have genotoxic potential associated with the generation by mining tailings. It was observed that in cities supplied hydric by the Doce river, or in relation to fishing, a CM increased after the collapse, suggesting a relationship between cancer mortality and water supply from the Doce river. However, studies are more studies to confirm this relationship.